2008
DOI: 10.1007/s12231-007-9003-6
|View full text |Cite
|
Sign up to set email alerts
|

Folk Classification, Perception, and Preferences of Baobab Products in West Africa: Consequences for Species Conservation and Improvement

Abstract: Folk Classification, Perception, and Preferences of Baobab Products in West Africa: Consequences for Species Conservation and Improvement. The present study is a component of a baobab (Adansonia digitata L.) domestication research program being undertaken in Benin, Burkina Faso, Ghana, and Senegal. Surveys conducted on a total of 129 women and 281 men of different ages included questions on perceptions and human/cultural meaning of morphological variation, use forms, preferences (desirable/ undesirable traits)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
95
0
11

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(114 citation statements)
references
References 7 publications
8
95
0
11
Order By: Relevance
“…This is concordant with many folk classifications all over the world. For example, Assogbadjo et al (2008) reported the use of morphological classification system for baobab (Adansonia digitata L.) in West Africa. Results from similar studies have revealed the critical importance of organoleptic properties of plants in folk classifications (Heinrich 1998, Newmaster et al 2006.…”
mentioning
confidence: 99%
“…This is concordant with many folk classifications all over the world. For example, Assogbadjo et al (2008) reported the use of morphological classification system for baobab (Adansonia digitata L.) in West Africa. Results from similar studies have revealed the critical importance of organoleptic properties of plants in folk classifications (Heinrich 1998, Newmaster et al 2006.…”
mentioning
confidence: 99%
“…However, there are concerns for the rapid land-use intensifications that may lead to increasing pressure on the species populations in the future. This is typically similar to other important species in the African landscape such as Adansonia digitata that is subjected to clearing for agricultural expansion and exploitation for other non-timber forest use (Assogbadjo et al 2008;Venter and Witkowski 2013).…”
Section: Socio-ecological Management Of Trees In Traditional Agroforementioning
confidence: 70%
“…In addition, the traditional cotton holders interviewed were classified by socio-ethnic group according to the classification of the National Institute of Statistics and Economic Analysis of Benin. Then, by categories of sex and age (man, woman, young, adult, old) from the structure proposed by Assogbadjo et al, (2008). This structure assumes that young people are between the ages of 30 and 40, adults are between the ages of 40 and 50, and the elderly are people who are older than 50.…”
Section: Discussionmentioning
confidence: 99%